2019
DOI: 10.1177/1354816619827712
|View full text |Cite
|
Sign up to set email alerts
|

ICT, infrastructure, and tourism development in Africa

Abstract: This study examines the relationship between information and communication technology (ICT), infrastructure, and tourism development in Africa between 1996 and 2016 using a dynamic panel gravity model. Our findings show that ICT and infrastructure have a positive, statistically significant relationship with tourism development; as ICT and infrastructure increase, the level of tourist arrivals also increases. This study also identifies relevant factors including bilateral real exchange rate and gross domestic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 77 publications
8
100
2
3
Order By: Relevance
“…The interest in determining and classifying tourism demand components has been increasing over the past few decades. In recent studies, the gravity model has been used for modeling and describing international tourism demand to determine its main components and features by illustrating tourism flows as trade of service (Adeola and Evans, 2019; Algieri, 2006; Eilat and Einav, 2004; Fourie et al, 2019; Lorde et al, 2015; Pintassilgo et al, 2016; Saayman et al, 2016; Seetanah et al, 2010; Xu et al, 2018). Other studies mostly estimate the determinants of tourism demand through linear or nonlinear models (Akis, 1998; Dogru et al, 2017; Dritsakis, 2004; Samitas et al, 2018; Santos and Cincera, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in determining and classifying tourism demand components has been increasing over the past few decades. In recent studies, the gravity model has been used for modeling and describing international tourism demand to determine its main components and features by illustrating tourism flows as trade of service (Adeola and Evans, 2019; Algieri, 2006; Eilat and Einav, 2004; Fourie et al, 2019; Lorde et al, 2015; Pintassilgo et al, 2016; Saayman et al, 2016; Seetanah et al, 2010; Xu et al, 2018). Other studies mostly estimate the determinants of tourism demand through linear or nonlinear models (Akis, 1998; Dogru et al, 2017; Dritsakis, 2004; Samitas et al, 2018; Santos and Cincera, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, observing the changes in determinants of tourism demand and putting required actions into practice are of importance for policymakers especially in countries with high tourist arrivals. To this end, tourism demand forecasts have become prominent, and many studies have focused on investigating tourism demand function of destinations (Adeola and Evans, 2019; Bassil et al, 2019; Dogru et al, 2017; Narayan, 2004; Song et al, 2019). Number of international tourist arrivals, tourism receipts, and number of nights in accommodation are the main measurements of international tourism demand which are primarily determined by per capita income, exchange rate, consumer price index (CPI), cost of transportation, and travel distance (Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The findings are consistent with Petti and Passiante (2009) found that ICT support infrastructure is one of the conditions for effective usage of ICT for managing destinations. Adeola and Evans (2019) found that ICT support infrastructure had a positive, statistically significant relationship with ICT usage for tourism development. Mtweve (2013) cited inadequate investment in innovation and infrastructure as a hurdle to the adoption of ICT at WHSs.…”
Section: Discussionmentioning
confidence: 95%
“…TOE theory provides a useful analytical framework in determining factors influencing ICT usage (Oliveira and Martin, 2011). The main assumptions of the theory is that decision to use new ICT system within the organization is determined by three (TOE) factors namely; technological, environmental and organizational factors (Adeola and Evans, 2019;Bahrini and Qaffas, 2018;Kante et al 2017;Kilangi, 2012;Kim and Kim 2018;Lama et al 2018;Wagaw and Mulugeta, 2018). Technological Factors (TF) refers to means of accessing, processing, and distributing volumes of data in the organization, and hence it aids thought process during decision-making (Gastelú et al 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation